Textual Cohesion in the Speech of Tariq ibn Ziyad at the Conquest of Andalusia: A Linguistic Study - Permana, Hengki; Raharja, Hatta; Syahid, Ahmad Habibi (Universitas Muhammadiyah Sumatera Barat, 2024)
This study examines textual cohesion in the speech of Tariq bin Ziyad delivered during the conquest of Andalusia in the 8th century. This speech is known as one of the psychological strategies that successfully inspired and motivated his troops in facing the larger Visigoth army. This study aims to identify and analyze the types of lexical and grammatical cohesion contained in the text of the speech. The research method used is descriptive qualitative with data sources in the form of speech texts of Tariq bin Ziyad taken from the internet. Data analysis is done by identifying, classifying, and interpreting sentences that contain lexical and grammatical cohesion. Lexical cohesion includes repetition, synonymy, antonymy, hyponymy collocation, and equivalence, while grammatical cohesion includes elements such as reference, substitution, ellipsis, and conjunction. The results show that Tariq bin Ziyad's speech contains various elements of cohesion that are effective in maintaining the unity and clarity of the message, as well as motivating and building solidarity among the troops. This textual cohesion plays an important role in effectively conveying the message and influencing the psychology of the listeners, which contributed to the military success of Tariq bin Ziyad and his troops in conquering Andalusia.